Enhancing Student Understanding of Heat Distribution in Metal Rods Through Interactive Learning Using Finite Difference Methods - Dewi, Nadia Puspa; Fadilah, Rahil Nurul; Palupi, Zahra Dinda; Satrio, Galih Dwi (Current STEAM and Education Research, 2024)
This study discusses the comparison of two finite difference methods, namely the explicit method and the Crank-Nicolson method (implicit), in simulating heat propagation in a metal rod. Heating is done by lighting a candle under the metal rod which is then extinguished after some time. This research aims to improve students' understanding of heat distribution in metal rods through an interactive method based on the Finite Difference Method, which is also expected to improve the ability to analyze and apply physics concepts in a practical context. The simulation results show that the explicit method requires very small time steps to achieve good stability, resulting in longer computation times. On the other hand, the Crank-Nicolson method demonstrates better and more consistent numerical stability, even with larger time intervals. Experimental modifications with varying time intervals show that the Crank-Nicolson method remains stable and provides more accurate results compared to the explicit method. Therefore, the Crank-Nicolson method is more recommended for long-term simulations requiring high stability and accuracy.